An In Vivo CRISPR Screen Identifies Stepwise Genetic Dependencies of Metastatic Progression - Scheidmann, Manuel C. (Cancer Res, 2022)
Blood-borne metastasis of breast cancer involves a series of tightly regulated sequential steps, including the growth of a primary tumor lesion, intravasation of circulating tumor cells (CTC), and adaptation in various distant metastatic sites. The genes orchestrating each of these steps are poorly understood in physiologically relevant contexts, owing to the rarity of experimental models that faithfully recapitulate the biology, growth kinetics, and tropism of human breast cancer. Here, we conducted an in vivo loss-of-function CRISPR screen in newly derived CTC xenografts, unique in their ability to spontaneously mirror the human disease, and identified specific genetic dependencies for each step of the metastatic process. Validation experiments revealed sensitivities to inhibitors that are already available, such as PLK1 inhibitors, to prevent CTC intravasation. Together, these findings present a new tool to reclassify driver genes involved in the spread of human cancer, providing insights into the biology of metastasis and paving the way to test targeted treatment approaches. SIGNIFICANCE: A loss-of-function CRISPR screen in human CTC-derived xenografts identifies genes critical for individual steps of the metastatic cascade, suggesting novel drivers and treatment opportunities for metastatic breast cancers.